Luminescence of MWO4 (M =Ca, Sr, Ba and Pb) prepared by solvothermal reaction - Titipun Thongtem (2018)
MWO4 (M = Ca, Sr, Ba and Pb) was solvothermally prepared using metallic nitrates and sodium tungstate in 25/5 volume ratios of glycerol/water (SGL) and propylene glycol/water (SPG) at 160°C for 6 h. XRD revealed the presence of MWO4 single phase with tetragonal scheelite structure. The strong W-O stretching band of WO4 tetrahedrons was detected at 705-875 cm-1. The product images show nano-sized particles in basic SGL and SPG solvents and flower-like particles in SPG solvent with pH of 6.7. Central peaks of the luminescent spectra are 445, 446, 443 and 440 nm, respectively.